Classified denoising method for laser point cloud data of stored grain bulk surface based on discrete wavelet threshold - Qing, Shao; Tao, Xu; Tatsuo, Yoshino; Nan, Song; Hang, Zhu (International Journal of Agricultural and Biological Engineering, 2016)
Surfaces of stored grain bulk are often reconstructed from organized point sets with noise by 3-D laser scanner in an online measuring system. As a result, denoising is an essential procedure in processing point cloud data for more accurate surface reconstruction and grain volume calculation. A classified denoising method was presented in this research for noise removal from point cloud data of the grain bulk surface. Based on the distribution characteristics of cloud point data, the noisy points were divided into three types: The first and second types of the noisy points were either sparse points or small point cloud data deviating and suspending from the main point cloud data, which could be deleted directly by a grid method; the third type of the noisy points was mixed with the main body of point cloud data, which were most difficult to distinguish. The point cloud data with those noisy points were projected into a horizontal plane. An image denoising method, discrete wavelet threshold (DWT) method, was applied to delete the third type of the noisy points. Three kinds of denoising methods including average filtering method, median filtering method and DWT method were applied respectively and compared for denoising the point cloud data. Experimental results show that the proposed method remains the most of the details and obtains the lowest average value of RMSE (Root Mean Square Error, 0.219) as well as the lowest relative error of grain volume (0.086%) compared with the other two methods. Furthermore, the proposed denoising method could not only achieve the aim of removing noisy points, but also improve self-adaptive ability according to the characteristics of point cloud data of grain bulk surface. The results from this research also indicate that the proposed method is effective for denoising noisy points and provides more accurate data for calculating grain volume. Keywords: point cloud data, denoising, grid method, discrete wavelet threshold (DWT) method, 3-D laser scanning, stored grain DOI: 10.3965/j.ijabe.20160904.2333 Citation: Shao Q, Xu T, Yoshino T, Song N, Zhu H. Classified denoising method for laser point cloud data of stored grain bulk surface based on discrete wavelet threshold. Int J Agric & Biol Eng, 2016; 9(4): 123－131.